The influence of effective use of mobile devices for learning outside the classroom: case study of secondary school students in Tanzania and South Africa - Mwapwele, Samwel Dick (Department of Information Systems, 2018)
There is an ongoing debate on whether students’ use of mobile devices extends to academic purposes. In developing countries, mobile devices are argued to assist in reducing digital divide and foster educational use leading to poverty alleviation. Framework on students’ effective use of mobile devices for learning outside the classroom (SEUMD) is applied as lens. This research investigates, what influence effective use of mobile devices for learning outside the classroom has on academic performance of secondary school students in Tanzania and South Africa. An Interpretive approach on multiple case studies is employed. A mixed method approach is used that includes, close ended questionnaires, semi-structured interviews and direct observations. A secondary school in Dar-es-salaam and a high school in Cape Town were selected for data collection. Data was collected with Form IV students and their teachers and Grade 12 learners and their teachers. Mixed method is applied to investigate students’ and teachers’ use of mobile devices for learning outside the classroom. Descriptive statistics is used to analyse questionnaires and thematic analysis for interviews and observations. Both, students’ and teachers’ use mobile device to socialize, recreational purposes, searching for information and academic purposes. On academic purposes, mobile devices are used to make phone calls, send short message services and on Internet. Internet use encompass websites, search engines, social networks and instant messaging applications. Students’ save pocket money to buy airtime and Internet bundles. Students’ receive advice and assistance from peers on mobile devices to acquire and technical help. Key findings demonstrate students’ effective use of mobile devices includes WhatsApp and Facebook to communicate to peers, friends and teachers on educational issues. Students’ assist peers by sending pictures, audio and video files that expound on topic of interest. Academic content acquired through other Internet sources is shared to groups students interact with. The use of SEUMD provides for a new framework that merges technology adoption, concerns in the society and providing a sustainable solution. SEUMD extends discussion on technology adoption by focusing on adopters’ goals and analysing sustainability of attaining the goal through effective use. Adoption of a technology is thus assessed as a process that starts before adoption and continues after through sustainability.